2022
DOI: 10.1136/gutjnl-2021-326482
|View full text |Cite
|
Sign up to set email alerts
|

Unfavourable intrauterine environment contributes to abnormal gut microbiome and metabolome in twins

Abstract: ObjectiveFetal growth restriction (FGR) is a devastating pregnancy complication that increases the risk of perinatal mortality and morbidity. This study aims to determine the combined and relative effects of genetic and intrauterine environments on neonatal microbial communities and to explore selective FGR-induced gut microbiota disruption, metabolic profile disturbances and possible outcomes.DesignWe profiled and compared the gut microbial colonisation of 150 pairs of twin neonates who were classified into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…Stool samples were collected from patients and donors in sterilized Eppendorf tubes and stored at −80°C. 59 These samples were used to extract microbial DNA for sequencing. The V4–V5 region of the bacterial 16S rRNA gene was amplified using Phusion High-Fidelity PCR Master Mix with HF buffer (New England Biolabs, England) and then sequenced on the Illumina MiSeq platform (Illumina, Inc.) using standard Illumina sequencing protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Stool samples were collected from patients and donors in sterilized Eppendorf tubes and stored at −80°C. 59 These samples were used to extract microbial DNA for sequencing. The V4–V5 region of the bacterial 16S rRNA gene was amplified using Phusion High-Fidelity PCR Master Mix with HF buffer (New England Biolabs, England) and then sequenced on the Illumina MiSeq platform (Illumina, Inc.) using standard Illumina sequencing protocols.…”
Section: Methodsmentioning
confidence: 99%
“…A study of 150 pairs of twins using 16S ribosomal RNA and metagenomic sequencing showed a correlation between increased bacterial diversity early in life and intrauterine FGR in twins. A reduction in Enterococcus and Acinetobacter numbers was observed in twin-born FGR infants and there was a lowering in the level of methionine and cysteine in stool samples taken after birth and after 2–3 years of follow-up [ 66 ]. It is also suspected that the level of cysteine in the stool may be correlated with the future physical development of the child [ 66 ].…”
Section: Fetal Growth Restrictionmentioning
confidence: 99%
“…A reduction in Enterococcus and Acinetobacter numbers was observed in twin-born FGR infants and there was a lowering in the level of methionine and cysteine in stool samples taken after birth and after 2–3 years of follow-up [ 66 ]. It is also suspected that the level of cysteine in the stool may be correlated with the future physical development of the child [ 66 ]. Oscillospira and Coprococcus participate in the synthesis of butyrate, which is an energy source for the epithelial cells of the small intestine, regulating glucose metabolism and reducing inflammation in the organism [ 67 ].…”
Section: Fetal Growth Restrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the properties of the microbiota of humans were largely a black box ( Cho and Blaser, 2012 ). And human symbiotic microbiota had a vital effect on the early and long-term neonatal physiological consequences ( Al-Shehri et al, 2016 ; Fujimura et al, 2016 ; Yang et al, 2022 ). For instance, the dysbiosis of the neonatal gut microbiome encouraged immune cell dysfunction related to childhood atopy ( Fujimura et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%